Pemisahan Ion Krom(III) dan Krom(IV) Dalam Larutan Dengan Menggunakan Biomassa Ganggang Hijau Spirogyra subsalsa Sebagai Biosorben. - Mawardi Mawardi; E. Munaf; S. Kosela; Widayanti Wibowo (Environmental Research Center (PPLH) of Udayana University, 2014)
Characteristic of biosorption of chromium(III) and chromium(VI) by green ganggange Spirogyrasubsalsa sp. biomass was investigated in a batch system. Based on FTIR spectroscopyspectra can be concluded that the biomass of green ganggange S. Subsalsa containingcarboxylate groups, amines, amides, amino, carbonyl and hydroxyl, in addition to thecompounds of silicon, sulfur and phosphorus. The results showed that the capacity biosorpsistrongly influenced by solution pH, contact time and initial concentration of the solution. Themaximum sorption of Cr3+ cations was seen at pH 4,0 and than constant at the higher pH. Biosorption of Cr6+, exist as Cr2O72- anion, decrease by increase of solution pH. The maximumbiosorption capacity for Cr3+ and Cr ions are 1.82 mg (0.035 mmol) and 1.51 mg (0.029 mmol)per gram of dry biomass, respectively. Rate of biosorption is relatively fast, with long intervalsof 30 minutes, each ion is absorbed approximately 95.7% and 86.5%. Absorption is alsoinfluenced by rapid mixing of biomass, while the factors of particle size and heating biosorbenbiomass absorption is less affected.